Peruvian business activity in the globalization process - Aranaga Manrique, David (2008)
The current process of world globalization, with its profound and intensive changes, has created in different societies the need to prepare strategically, emphasizing their actions in the training of human resources, corporate business organization and technological innovation, in such a way that so that it can compete with manufactured products that will be exported, with efficiency, high productivity and quality.